Adjusting to my School (2016)
ABSTRACT: This action research project intended to explore how the English class favors both first graders’ learning of English and their adjustment to elementary school. This study was conducted at Institución Educativa Normal Superior de Envigado in a first grade class. Data were collected through class observations recorded on a reflective journal, two focus group interviews to students and an interview to the cooperating teacher. Outcomes revealed that through the creation of routines and setting rules the students adapt better to the new change they experience when they turn from preschool to elementary education. Moreover, the development of a democratic classroom contributes to the creation of a favorable atmosphere necessary to facilitate student’s learning and improvements on their behavior.